2018
DOI: 10.3390/ijms19123849
|View full text |Cite
|
Sign up to set email alerts
|

Editorial for Special Issue “Plant Mitochondria”

Abstract: The primary function of mitochondria is respiration, where catabolism of substrates is coupled to adenosine triphosphate (ATP) synthesis via oxidative phosphorylation (OxPhos). [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Mitochondria customarily play a central role in plant metabolism as a major source of adenosine triphosphate (ATP) [20,21]. Seeds are largely dependent on mitochondrial respiration to provide obligatory energy for their germination [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria customarily play a central role in plant metabolism as a major source of adenosine triphosphate (ATP) [20,21]. Seeds are largely dependent on mitochondrial respiration to provide obligatory energy for their germination [22].…”
Section: Introductionmentioning
confidence: 99%
“…When the substrates NADH and succinate are oxidized, electrons are transferred from complexes I and II to complex III via coenzyme-Q (CoQ), from complex III to complex IV via cytochrome c, and finally, to O2. During this process, the protons (H + ) in the mitochondrial matrix are pumped to the intermembrane space, resulting in a proton electrochemical potential coupled to the conversion of adenosine diphosphate (ADP) and Pi to ATP, catalyzed by complex V [ 43 ]. In the current transcriptome, no complex II subunits ( sdh3 and sdh4 ) were detected, this is consistent with the loss of the two genes in the mitochondrial genomes of other grasses ( Table S7 ), suggesting that CoQ can only obtain electrons from complex I.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, mitochondrial respiration was obviously enhanced in spring shoots ( Figure 1 g), and mitochondrial transcriptome analysis showed that all enzymes involved in OXPHOS (functioning by electron transfer chain) were upregulated at the spring shoot stage ( Figure 3 a), including NADH dehydrogenase (complex I), cytochrome reductase (complex III), cytochrome oxidase (complex IV) and ATP synthase (complex V). In the process of intracellular energy conversion, ATP synthase is a key enzyme existing in the mitochondrial inner membrane that synthesizes ATP in large quantities using the proton gradient and related membrane potential [ 43 ]. In mitochondrial proteome analysis, three ATP synthase proteins (PMA, ATPF1E and ATPeF1B) were also identified to be significantly upregulated ( Table 2 ), suggesting that OXPHOS, as the main method of energy production, met the energy demand for fast-growth initiation of spring shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Both I1K3U8 and C6SZ93 proteins participate in the carbohydrate metabolism pathway which is essential for plant response to abiotic stress including low-P ( Singh and Singh 1968 ; Rychter and Randall 1994 ; Rosa et al 2009 ). I1KW20 contributes to mitochondrial biogenesis which is a specific pathway that supports photosynthetic processes and enables continuous survival during abiotic stress exposure in plants ( Ahn et al 2006 ; Welchen et al 2014 ; Taylor 2018 ). Upregulation of proteins in these pathways as observed in L13 may have favoured the low-P tolerance.…”
Section: Discussionmentioning
confidence: 99%